Le paysage, structure urbaine et mentale du patrimoine culturel. L’exemple de Bologne - Lucas Marolleau (Bulletin de l’Association de Géographes Français)
The aim of this paper is to the question of a historic centre’s “heritagisation” on the basis of the landscape concept. Through an interdisciplinary approach, it is possible to identify the end of the 1950’s and the 1960’s as a turning point in the patrimonial politics of Bologna’s municipality: at that time, the landscape became for the inhabitants a way to demand the conservation of the old centre. Its local representations can be used as a way to understand its role in the “heritagisation” process. This role is accentuated at Bologna by the morphological inertia of the historic centre which pertains to the inhabitant’s spatiality and “patrimoniality”. The landscape is therefore an entry point for distinguishing its own “heritagisation” from that of exceptional objects.